Sexual activity among female teenagers: a comparison between two groups of middle class adolescents from a private clinic according to pregnancy status - Faisal-Cury,Alexandre (2008)
OBJECTIVES: to investigate patterns of sexual activity among teenagers. METHODS: a cross-sectional study was conducted between July 1998 and September 2000, among 117 sexually active female adolescents from a private clinic, in the city of the Osasco, State of São Paulo, Brazil. They were divided into two groups: one pregnant group (PG) comprised 62 adolescents that were either pregnant (46) or had previously been pregnant (16); another group of 55 female adolescents that had never been pregnant (NPG). During consultations with these subjects, a physician conducted a semi-structured interview. Knowledge, attitudes and practices relating to sexual activity were evaluated. The comparison between the two groups was carried out using Student's t test, the chi-square test or Fisher's exact test. RESULTS: the two groups showed considerable similarities in terms of sexual behaviour, having engaged in the first sexual intercourse at the age of 15 and having had an average number of sexual partners of 1.5. Nevertheless, adolescents in the PG group had initiated sexual life earlier and tended to use less contraceptive methods during the first intercourse. Despite widespread knowledge of contraception, a large number of the adolescents did not use any contraceptive method during first sexual intercourse. In their current sexual life, an average of 81% of the participants referred to attaining orgasm. CONCLUSIONS: knowledge about contraceptive techniques is not enough to avoid unplanned pregnancies, suggesting the importance of investigating other psychosocial aspects of motherhood and maternal identity among teenagers.